Analysis of the effectiveness of virtual reality exposure therapy on the balance of Parkinson's patients: integrative review (Research, Society and Development, 2022)
The Virtual Reality Exposure Therapy is a technique that allows interaction between the individual and a computational system that recreates reality in a virtual interface, offering cognitive and motor training concomitantly.  Thus, physiotherapy is increasingly using this method for the treatment of PD, which has been demonstrated in several studies.  Therefore, the present study aimed to know the effects of gametherapy on the balance of individuals with Parkinson's disease through an integrative literature review, using the databases VHL (Virtual Health Library), SciELO (Scientific Electronic Library Online), PubMed and PEDro, with the search for studies published between the years 2016 and 2021,  using descriptors according to DeCS/MeSH: "Parkinson's disease" AND "Virtual reality exposure therapy" OR " Gametherapy" OR "Video Game" and their respective translations into English. After methodological analysis, 05 articles were included that were the objective of this study. The results showed that the rehabilitation of Parkinson's patients through virtual reality exposure therapy proved to be an effective tool in improving body balance and functional capacity, demonstrating potential in reducing the risk of falls, increasing self-confidence and improving the quality of life of patients, however, it is not clear whether this modality is more effective than conventional physiotherapy. It is emphasized the need for further studies with greater methodological rigor.